Analysis of glass fibre reinforced epoxy composite hovercraft hull base - Abdul Kadir, Amiruddin; Salit, Mohd Sapuan; Jaafar, Abdul Aziz (Elsevier, 2008)
The use of corrosion resistant and lower density composite has made it one of the choices for this weight sensitive application. Structural analysis was done in this research on the suitability and reliability of the composite for the hovercraft hull base by using NASTRAN/PATRAN software. The future recommendation in constructing the base hull prototype from composite was supported by the results from this analysis and simulations of the composite usage. The finding supported the fact that weight played a significant role in designing a hovercraft as the hull must be strong to withstand the pressure applied yet still remain light.